Vancomycin-Resistant Enterococcal Meningitis, Disseminated Strongyloidiasis, and Hypogammaglobulinemia. Issue 6 (November 2017) - Uyemura, Trevor M.; Siegel, Marc O.; Lucar, Jose; Simon, Gary L.
Abstract : Abstract: The role of immunoglobulins in control of strongyloidiasis has not been well appreciated. This case of disseminated strongyloidiasis with vancomycin-resistant Enterococcus faecium meningitis illustrates the critical role of immunoglobulins in preventing the Strongyloides hyperinfection syndrome. Abstract : Disseminated stronyloidiasis infection is usually associated with concommitant steroid therapy or HTLV-1 infection. The role of immunoglobulins in preventing this condition has not been well-recognized. The diagnosis may be missed in patients who lack the traditional risk factors. The important role of immunoglobulins in this condition help to explain why HIV is not a major risk factor for disseminated strongyloidiasis since HIV is primarily a cell-mediated immune deficiency and not a humoral deficiency.